Topological Conjugate for Some Maps - Dunia Muhammed Kreem ALftllawy; Batool Hatem Akar Alkfari (Genius Journals, 2022)
Topological conjugation in dynamical systems is of great interest in the study. We have shown that there are chaotic characteristics that can be transferred from one function to another if there is a topological conjugate between the two functions, which serves us in studying some chaotic functions. As the conjugacy between the Tent map , quadratic map and shift map .There is also topological conjugate between other maps, for example, the Bernoulli map and the logistic map are topological conjugate. And the shift map on the space of two –sided sequences in two symbols is topologically conjugate or semi conjugate to the Henon map.
Keywords: Topological conjugate; Tent; quadratic